Transforming ERP Transactions Using SAP And Robotic Process Automation (RPA) - Viswanathan, Jeyaganesh (International Journal of Computer Sciences and Engineering, 2024)
This research investigates the integration of SAP ERP with Robotic Process Automation (RPA) and Power Apps to address specific challenges in field service operations, particularly in remote areas with unreliable internet connectivity. The solution leverages SAP`s ERP capabilities and RPA to enable seamless offline data capture, synchronization, and automated processing of service transactions. Field technicians visiting customer sites use mobile devices to capture data (e.g., repair parts orders) immediately in the system offline, thus reducing errors and improving accuracy. This paper details how data is captured both online and offline and how it synchronizes with SAP ERP upon reconnection, triggering RPA bots to create shipment orders and update inventory, thereby streamlining the workflow. The study explores concrete implementation strategies like offline-capable SAP interfaces, external database integration, and optimized automated workflow management. SAP ERP and RPA integration significantly enhances efficiency, minimizes manual intervention, and improves service delivery in low-connectivity environments. Evaluations show quantifiable improvements in transaction times, data integrity, and service quality, ultimately leading to increased customer satisfaction. The findings demonstrate the broad scalability of this approach across industries, optimizing ERP use in remote operations. The framework provides a practical model for organizations seeking to enhance SAP ERP, reduce costs, and overcome connectivity barriers in field service management. Keywords: SAP ERP, Robotic Process Automation (RPA), Offline Data Capture, Data Synchronization, Automated Transaction Processing, Service Delivery Improvement, Operational Efficiency, SAP Integration, Field Service Management.